Pengembangan Aplikasi Cam Alternatif - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The widely use of Computer Numerically Controlled machine on manufacturing process, make production speed run with smaller cost and faster time than before. Computer Numerically Controlled machine or CNC machine can created object with exact shape and measurement from virtual model which created from computer aided manufaturing application or CAM application. Because of the same standard for some CNC machine hardware application, CAM application can be develop widely not only from internal machine application. By developing new CAM application can give few benefits like low cost development, optimizing work of CNC machine, decrease CNC machine running time and many more. The simpliest way for creating new CAM application by using CAD application as CAM application. The popular CAD application like AutoCAD have internal programing application for advance development. By using this application, AutoCAD will have new functionality not only as CAD application but as CAM application.